2017
DOI: 10.1186/s13102-017-0075-z
|View full text |Cite
|
Sign up to set email alerts
|

Are there two forms of isometric muscle action? Results of the experimental study support a distinction between a holding and a pushing isometric muscle function

Abstract: BackgroundIn isometric muscle function, there are subjectively two different modes of performance: one can either hold isometrically – thus resist an impacting force – or push isometrically – therefore work against a stable resistance. The purpose of this study is to investigate whether or not two different isometric muscle actions – the holding vs. pushing one (HIMA vs PIMA) – can be distinguished by objective parameters.MethodsTen subjects performed two different measuring modes at 80% of MVC realized by a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
95
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(99 citation statements)
references
References 39 publications
3
95
1
Order By: Relevance
“…As previously mentioned, the body of literature examining the characteristics of "pushing," "holding," and "quasi" isometric actions is growing. [54][55][56][57][58][59][60]78 However, there is a paucity of long-term experimental studies examining these isometric contraction subsets.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously mentioned, the body of literature examining the characteristics of "pushing," "holding," and "quasi" isometric actions is growing. [54][55][56][57][58][59][60]78 However, there is a paucity of long-term experimental studies examining these isometric contraction subsets.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…53 Additionally, emerging research has demonstrated unique neuromuscular characteristics between "pushing" (ie, exerting force against an immovable object) and "holding" (ie, maintaining a joint position while resisting an external force) isometric contractions. [54][55][56][57][58][59][60] Understanding the loading parameters that achieve a desired adaptive response in muscle and tendon would be of benefit to practitioners. Therefore, the purpose of this review was to systematically evaluate research directly comparing the outcomes of isometric training variations and to provide training guidelines for a variety of desired outcomes.…”
mentioning
confidence: 99%
“…However, the MTG of triceps tendon showed a significantly higher power in the frequency ranges of 10 to 29 Hz and 8 to 15 Hz, respectively, during HIMA compared to PIMA. [1] This is opposite to the findings of Hunter et al [7], who found a higher power during PIMA. The differences might be attributed to the different settings and, of course, different methods (EMG vs. MMG).…”
Section: Introductionmentioning
confidence: 66%
“…Usually isometric muscle action is measured by pushing against a stable resistance. Subjectively, however, one can perform isometric muscle action by pushing against a stable recently published study [1] of our laboratory partly supported those results, partly disagreed with them. The setting included the recordings of mechanomyography (MMG) of the triceps brachii and the abdominal external oblique muscles as well as of mechanotendography (MTG) of the triceps brachii tendon, whereas no EMG was captured.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation